Pylorus- and vagus-nerve-preserving partial gastrectomy (D2 dissection) - Zhang, Jian; Cao, Liang; Wang, Zhenglin; Zhang, Chi; Hu, Xiang (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
Pylorus- and vagus nerve-preserving partial gastrectomy is important in improving the prognosis of early gastric cancer surgery, reducing surgical complications and improving the quality of life for such patients. In the present case, pylorus- and vagus nerve-preserving partial gastrectomy was performed using the bipolar electrocautery dissection technique combined with D2 dissection along the lesser sac.